Biodegradation of Natural and Waste Water by Hydrocarbon-Oxidizing Microorganisms with Various Sorbents Contaminated with Spent Mineral, Semi-Synthetic and Synthetic Lubricating Oils - Ganiev I.M. (Innovations in Biological Science Vol. 9, 2024)
Aims: Study of processes of degradation of spent mineral, semisynthetic and synthetic motor oils by selected hydrocarbon-oxidizing microorganisms and selection of sorbents contributing to the optimization of processes of decontamination of natural and wastewater from these types of pollutants. Study Design: Studies were conducted on controlled biodegradation with mineral, semi-synthetic and synthetic lubricating oils with a consortium of nine types of hydrocarbons oxidizing microorganisms (HOM), in concentrations with initial contamination of 90 ± 6, 400 ± 6 and 1000 ± 6 mg/dm3 per 400 cm3 of runoff under statistical conditions at temperatures from +16 to +29 °C. The growth in the number of microorganisms was within 304 • 106 – 306 • 106 cl/cm3 (with continuous cleaning mode – in 14 days). Also, in the experiment on the biodegradation of lubricating oils, HOM sorbing materials were used: river sand, coal powder, polyethylene chips, crushed Tetra Pak, sawdust and peat (natural sizes), husks (buckwheat, barley, wheat and oats) with particle sizes - 0.017; 0.034; 0.07 and 0.1 mm. Their concentration was (depending on the test series) 10, 20, 30, 40, 50 and up to 100 mg/dm3. Methodology: Nine main bacterial strains, together with various sorbents isolated from various industrial sewers, were used for the biodegradation of natural and wastewater that were contaminated with spent mineral, semi-synthetic and synthetic lubricating oils. Microorganisms from environmental objects were isolated by direct seeding and by the method of cumulative cultures. For comparison, different cultures of Alcaligenes (1 species), Micrococcus (1 species), Brevibacterium (2 species), Bacillus (1 species), Flavobacterium (1 species), Clostridium (1 species) and Pseudomonas (2 species), which are part of the oil- and oil-destroying microbiological consortium, were used. Microorganisms are united in consortia according to morphological, physiological and biochemical properties and are represented by both gram-positive and gram-negative, mobile and stationary aerobic and facultative anaerobic forms. The physiological activity of the strains is variable, and their enzymatic activity is high. The degree of biotransformation of wastewater was assessed by the dynamics of chemical oxygen consumption (COC), biological oxygen consumption (BOC5) and dissolved oxygen (O2) in the process of biodegradation of wastewater pollution by chemical methods. Results: In the presence of sorbents (husks of grain crops) with microorganisms involved in the purification of water from transformer oil, the process of habituation was revealed in the interval from 1 to 3 days of contact and diesel oil, respectively, up to 3 days. At the same time, the increase in the number of transformer oil reaches 10-12 times in the variant with buckwheat and oat husks, and up to 18 times in the presence of barley husks in water, and the increase in the number of diesel oil reaches 2-3 times in the variants with wheat and barley husks. According to the dynamics, the increase in the number of HOM in semi-synthetic oil in the presence of grain husks reduces pollution in concentrations from 50 mg/dm3 and reaches 55.0 - 63.7% by 6-9 days. The proportion of mineral oils subject to biodegradation of HOM, in the same period, exceeds more than 30%. The overall cleansing effect in the variants with oat husks reaches 90.6%, barley 92.2%, and buckwheat and wheat 93.7 - 93.8%. Whereas the efficiency of water purification from used lubricating oils in the presence of river sand, polyethylene shavings, grasses, coal powder and peat remained at or below the levels observed under the influence of HOM. Conclusion: In the biodegradation of natural and wastewater from oil pollution, sorbents can be used through optimization with HOM, leading to the achievement of the maximum permissible standard for water purification from used lubricating oils. Thus, we recommend the controlled use of sorbents of grain crops, such as oat husks, wheat, barley and buckwheat (particle size 0.017-0.034 mm with a concentration of 50 mg/dm3) together with HOM (up to 350 • 106 kl/cm3).